1962
DOI: 10.1001/jama.1962.03050350027006
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Evaluation of Surgical Patients

Abstract: After operation, the patients were examined daily.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
4

Year Published

1965
1965
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(39 citation statements)
references
References 7 publications
1
33
0
4
Order By: Relevance
“…1998;133:194-198 P ULMONARY complications following surgery are associated with significant morbidity [1][2][3][4] and have been shown to increase the length of hospitalization. 1,5,6 The identification of patientrelated features associated with increased risk for postoperative pulmonary complications (PPCs) has been reported; however, the results have been conflicting. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Surgical features that increase risk include the performance of emergent procedures; longer anesthesia duration; and the surgical incision site, with thoracic and upper abdominal incisions having the highest rate of PPCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1998;133:194-198 P ULMONARY complications following surgery are associated with significant morbidity [1][2][3][4] and have been shown to increase the length of hospitalization. 1,5,6 The identification of patientrelated features associated with increased risk for postoperative pulmonary complications (PPCs) has been reported; however, the results have been conflicting. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Surgical features that increase risk include the performance of emergent procedures; longer anesthesia duration; and the surgical incision site, with thoracic and upper abdominal incisions having the highest rate of PPCs.…”
Section: Discussionmentioning
confidence: 99%
“…5,10,18,20,33 Although smokers are more likely to produce sputum, not all smokers have productive coughs and smoking history is not a reliable predictor of PPCs. We found no association between spirometric results and PPCs, similar to the results of other studies.…”
Section: Commentmentioning
confidence: 99%
“…Spirometry is also helpful in determining whether patients with COPD or asthma are under optimal control before surgery. Early studies indicated that a partial pressure of arterial carbon dioxide (PaCO 2 ) greater than 45 mm Hg increases the risk of PPCs [71, 72]. However, later studies have not shown the association between a raised PaCO 2 and the PPCs risk [73].…”
Section: Risk Factors For Ppcsmentioning
confidence: 99%
“…Lung function tests done prior to surgery have been used for decades to assist in estimating surgical risk 3 . Spirometry measures the volume of inhaled and exhaled air and respiratory flows, being especially useful in the analysis of data derived from forced expiratory maneuver and the peak expiratory flow (PEF).…”
Section: Introductionmentioning
confidence: 99%